Methotrexate-Lactoferrin Targeted Exemestane Cubosomes for Synergistic Breast Cancer Therapy - Mokhtar, Sarah; Khattab, Sherine N.; Elkhodairy, Kadria A.; Teleb, Mohamed; Bekhit, Adnan A.; Elzoghby, Ahmed O.; Sallam, Marwa A. (Frontiers in Chemistry, 2022)
While the treatment regimen of certain types of breast cancer involves a combination of hormonal and chemotherapy, the outcomes are limited due to the difference in the pharmacokinetics of both treatments agents that hinders their simultaneous and selective delivery to the cancer cells. Herein we report a hybrid carrier system for the simultaneous targeted delivery of aromatase inhibitor exemestane (EXE) and methotrexate (MTX). EXE was physically loaded within liquid crystalline nanoparticles (LCNPs), while MTX was chemically conjugated to lactoferrin (Lf) by carbodiimide reaction. The anionic EXE-loaded LCNPs was then coated by the cationic MTX-Lf conjugate via electrostatic interactions. The Lf-targeted dual drug loaded LCNPs exhibited a particle size of 143.6±3.24 nm with polydispersity index of 0.180. It showed excellent drug loading with EXE encapsulation efficiency of 95% and MTX conjugation efficiency of 33.33%. EXE and MTX showed synergistic effect against MCF-7 breast cancer cell line with a combination index (CI) 0.342. Furthermore, the Lf-targeted dual drug loaded LCNPs demonstrated superior synergistic cytotoxic activity with a combination index (CI) of 0.242 and a dose reduction index (DRI) of 34.14 and 4.7 for EXE and MTX, respectively. Cellular uptake studies demonstrated higher cellular uptake of Lf-targeted LCNPs into MCF-7 cancer cells than non-targeted LCNPs after 4 and 24 hours. Collectively, the targeted dual drug loaded LCNPs is a promising candidate offering combinational hormonal /chemotherapy for breast cancer.